Comparative Effects of Moderate vs. High-Intensity Aerobic Exercise on Abdominal Fat, Liver Enzymes, and Intrahepatic Fat in 105 Obese Adolescents Aged 10–19 Years: A Prospective Cohort Study (2022–2024) (Development Engineering Conferences Center Articles Database, 2025)
Background and Aim: Childhood obesity is a global epidemic, with 20–30% of adolescents exhibiting hepatic steatosis and metabolic dysfunction. While aerobic exercise is recommended, the optimal type and intensity remain unclear. This study compares the long-term effects of moderate-intensity continuous training (MICT) vs. high-intensity interval training (HIIT) on abdominal adiposity, liver enzymes, and intrahepatic fat in obese adolescents.Methods: A prospective cohort of 105 obese adolescents (BMI ≥95th percentile, aged 10–19) was recruited from the Tabriz Pediatric Obesity Clinic (2022–2024). Participants self-selected into:• HIIT Group (n=52): 4 sessions/week of cycling/running intervals (80–90% max heart rate).• MICT Group (n=53): 5 sessions/week of brisk walking/cycling (60–70% max heart rate).Outcomes included changes in visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), intrahepatic fat (IHF, MRI-PDFF), liver enzymes (ALT, AST, GGT), and gut microbiota composition (16S rRNA sequencing). Data were analyzed using SPSS v28 and STATA v17, with significance at p < 0.05.Results:VAT Reduction: HIIT group: −18.2% vs. MICT: −9.5% (p = 0.001).IHF Reduction: HIIT: −27.4% vs. MICT: −14.8% (p = 0.003).Liver Enzymes: ALT decreased by 35% in HIIT vs. 18% in MICT (p = 0.01).Microbiota: HIIT increased Akkermansia (+2.1-fold, p = 0.002) and reduced Firmicutes/Bacteroidetes ratio (OR: 0.3, 95% CI: 0.1–0.7)Conclusion: HIIT significantly outperformed MICT in reducing abdominal and hepatic fat, improving liver function, and modulating gut microbiota. Adolescents in the HIIT group achieved 65% resolution of hepatic steatosis vs. 32% in MICT (p = 0.001). These findings advocate for HIIT as a frontline intervention in pediatric obesity management.